The paradox of faith and „logic“ of nihilism: S. Kierkegaard - Šerpytytė, Rita (Religija ir kultūra, 2007)
Selection of the starting point performed by contemporary philosophy, which raises a question of nihilism, swings between the two theoretical perspectives, i. e. nihilism as spiritual event and nihilism as speculative „event“. In such conceptual horizon we face the question on the interconnection of the thinking of individual authors with the context of nihilism. This article discusses the possibility of attaching the author who was not announcer or theoretician of nihilism – Kierkeggard – to the history of nihilism. Thus, the field of the discussions on nihilism embraces not only the ontological topic, but also the problem of „logic“ of nihilism.